LinkAja Business Models Strategy Development Using BMC Approaches - Novreyna Alda; Sari Wulandari (School of Industrial and System Engineering, Telkom University, 2020)
In the first quarter of 2019, there was an increase in the value and the volume transaction onelectronic money transactions in Indonesia. The development of electronic money is directlyproportional to the high competition of companies engaged in the field of mobile payment.LinkAja is a mobile payment application product that is representative of collaborationbetween Telkomsel and the number of State-Owned Enterprises (SOEs). One of the keys tosuccess in facing competition is to develop continuously. Therefore, it is necessary to developthe right business model to determine the optimal strategy in developing the LinkAjaapplication business. The objectives of this research are formulating and developing LinkAjabusiness models strategy. This result of this study proposed business model in the form ofimprovement for each element of its business model including: elements (1) Customersegments: Adding target customers to e-marketplaces and e-commerce, (2) Customerrelationships: Developing cooperation with LinkAja competitors, (3) Value Proposition:Developing customer consulting services by providing training for using the LinkAjaapplication, (4) Key Activities: Developing collaboration with partners and competitors, (5)Key Partners: Collaborating with the competitors such as Gopay, OVO, FUND, etc., (6) KeyResources: Using digital budget information systems to facilitate transparency of companybudgets, (7) Revenue streams: Upgrading fees for premium services, and (8) Cost Structure:Research costs.